Gut-Brain Axis: Exploring the Link Between Digestive Health and Mental Health - Khan, Muhammad Riaz; Ahmad, Ishaq; Farooq, Muhammad; Khan, Muhammad Adnan; Khan, Asma; Farman Ullah, (Indus Journal of Bioscience Research, 2024)
Objective: This study aimed to explore the link between digestive health and mental well-being through the gut-brain axis, with a focus on microbial composition, dietary patterns, and psychological outcomes in a local population. Methodology: A retrospective study was conducted at the Hayatabad Medical Complex, Peshawar, between April 2022 to March 2023. A total of 323 participants were included, with 162 patients having gastrointestinal disorders and 161 controls. Data on demographics, dietary patterns, microbial composition, and psychological well-being were analyzed. Independent t-tests and chi-square tests were used for statistical analysis, with a significance level set at p < 0.05. Results: Patients with gastrointestinal disorders exhibited significantly higher anxiety (11.2 ± 4.5 vs. 6.8 ± 3.9, p < 0.001) and depression scores (10.4 ± 4.1 vs. 5.7 ± 3.5, p < 0.001) compared to controls. Microbial dysbiosis was more prevalent in the gastrointestinal disorder group (63%) than in controls (32%, p < 0.001). Traditional dietary patterns were associated with gastrointestinal disorders (p = 0.032). Demographics showed no significant differences in age (p = 0.246) or sex (p = 0.431). Conclusion: The findings confirm a strong association between gut health and mental well-being, emphasizing the role of microbial dysbiosis and dietary patterns. The study highlights the need for gut-targeted therapies and public health initiatives to address the gut-brain axis.